Doxorubicin-Conjugated Iron Oxide Nanoparticles: Surface Engineering and Biomedical Investigation - Oleksa, Viktoriia; Macková, Hana; Patsula, Vitalii; Dydowiczová, Aneta; Janoušková, Olga; Horák, Daniel (ChemPlusChem, 2020)
Development of therapeutic systems to treat glioblastoma, the most common and aggressive brain tumor, belongs to priority tasks in cancer research. We have synthesized colloidally stable magnetic nanoparticles (Dh =336 nm) coated with doxorubicin (Dox) conjugated copolymers of N,N-dimethylacrylamide and either N-acryloylglycine methyl ester or N-acryloylmethyl 6-aminohexanoate. The terminal carboxyl groups of the copolymers were reacted with alendronate by carbodiimide formation. Methyl ester groups were then transferred to hydrazides for binding Dox by a hydrolytically labile hydrazone bond. The polymers were subsequently bound on the magnetic nanoparticles through bisphosphonate terminal groups. Finally, the anticancer effect of the Dox-conjugated particles was investigated using the U-87 glioblastoma cell line in terms of particle internalization and cell viability, which decreased to almost zero at a concentration of 100 μg of particles per ml. These results confirmed that poly(N,N-dimethylacrylamide)-coated magnetic nanoparticles can serve as a solid support for Dox delivery to glioblastoma cells.
Keywords: nanoparticles; drug delivery; doxorubicin; povrchové vlastnosti; viabilita buněk; Acrylic Resins; protinádorové látky; Cell Line, Tumor; Drug Screening Assays, Antitumor; akrylové pryskyřice; Cell Survival; Magnetite Nanoparticles; Drug Carriers; antitumor agents; magnetické nanočástice; magnetic properties; lidé; cytotoxicity; Humans; Surface Properties; Drug Liberation; screeningové testy protinádorových léčiv; uvolňování léčiv; nádorové buněčné linie; nosiče léků; Doxorubicin; Antineoplastic Agents